Zakir Naik’s Concept of Divinity-Cosmology: Criticism-Reconstruction of the Modern Natural-Cosmological Theology - Gigih Saputra (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2020)
Zakir Naik voices the evidence of God’s existence by employing the Big Bang Theory while proving the truth of al-Qur’ān. His positive reputation and controversy also create an impact on his da’wa journey. This study aims to bring out criticism and reconstruction on the concept of Zakir Naik’s cosmology and argument of God’s existence. The author, therefore, uses the Big Bang theory, al-Kindī’s Natural Theology, and Peter Kreeft’s Kalam Cosmology Argument. The result of the research shows the irrelevance of Zakir Naik’s explanations to the Big Bang theory itself, in addition to his lack of exposition about the theory. His idea, in fact, only centers around the proof of God’s existence as well as the truth of al-Qur’ān. Philosophically, this suggests that his concept of creation is inadequate. This, moreover, indicates that the explanation of the infinity of causality and the Infinite Regress critiques are too classic. The article attempts to reconstruct the Big Bang Theory to be more pertinent and profound and also to reform atheism cosmology. The attempt includes strengthening the position of Creatio ex Nihilo based on al-Kindī’s Natural Theology and its comparison to the other theory, such as Emanationism. Additionally, it is to extend the argument of causality and the criticisms toward Infinite Regression with the argumentation development based on al-Kindi’s Theology and Peter Kreeft’s Kalam Cosmology.